Products of stochastic matrices and applications - Harry Cohn (International Journal of Mathematics and Mathematical Sciences)
This paper deals with aspects of the limit behaviour of products of nonidentical finite or countable stochastic matrices (Pn). Applications are given to nonhomogeneous Markov models as positive chains, some classes of finite chains considered by Doeblin and weakly ergodic chains.